Vpliv univerze na razvoj Ljubljane - Pak, Mirko (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 1997)
The University of ljubljana, founded in 1919, includes 27 faculties and higher schools, as well as some academies of art, with 33,000 students altogether. After the 2nd World War, the only Slovenian University influenced the development of Ljubljana for many years: (1) its institutions occupy a significant part of town areas and represent some specific elements of town development (spatial and functional), which is evident from their locations; (2) it has significantly influenced with its employees and students the economic stucture of the town; (3) it is integrated in the socio-cultural structure of the town; (4) it has influenced the concentration of research capacities and institutions with its scientific and research activities.
Keywords: Ljubljana; mesta; University of Ljubljana; Univerza v Ljubljani; univerze; urbana geografija